Current Nanoparticle Approaches in Nose to Brain Drug Delivery and Anticancer Therapy - A Review - Ansari, Mohammad A.; Chung, Ill-Min; Rajakumar, Govindasamy; Alzohairy, Mohammad A.; Alomary, Mohammad N.; Thiruvengadam, Muthu; Pottoo, Faheem H.; Ahmad, Niyaz (Current Pharmaceutical Design, 2020)
Nanoparticles (NPs) are unique may be organic or inorganic, play a vital role in the development of drug delivery targeting the central nervous system (CNS). Intranasal drug delivery has shown to be an efficient strategy with attractive application for drug delivery to the CNS related diseases, such as Parkinson's disease, Alzheimer 's disease and brain solid tumors. Blood brain barrier (BBB) and blood-cerebrospinal fluid barriers are natural protective hindrances for entry of drug molecules into the CNS. Nanoparticles exhibit excellent intruding capacity for therapeutic agents and overcome protective barriers. By using nanotechnology based NPs targeted, drug delivery can be improved across BBB with discharge drugs in a controlled manner. NPs confer safe from degradation phenomenon. Several kinds of NPs are used for nose to the brain (N2B) enroute, such as lipidemic nanoparticles, polymeric nanoparticles, inorganic NPs, solid lipid NPs, dendrimers. Among them, popular lipidemic and polymeric NPs are discussed, and their participation in anti-cancer activity has also been highlighted in this review.
Keywords: nose to brain drug delivery